In Situ Reproductive Bioassay with Caged Gammarus fossarum (Crustacea): Part 1—Gauging the Confounding Influence of Temperature and Water Hardness. (5th February 2020) - Chaumot, Arnaud; Coulaud, Romain; Adam, Olivier; Quéau, Hervé; Lopes, Christelle; Geffard, Olivier
Abstract: Monitoring the adverse effects of environmental contaminants on the reproduction of invertebrate species in the field remains a challenge in aquatic ecotoxicology. To meet the need for reliable tools for in situ toxicity assessment, we present the first part of a methodological study of the in situ implementation of a reproductive bioassay in Gammarus previously developed for screening the toxicity of chemical compounds during laboratory exposure. To ensure the correct interpretation of the modulation of reproductive markers (molting, fecundity, follicle growth, and embryonic development) in uncontrolled environmental conditions, we experimentally assessed and statistically modeled the variability in the female reproductive cycle during laboratory exposure under several temperature and water hardness conditions. Whereas water hardness did not influence the reproductive cycle, the significant accelerating effect of temperature on the dynamics of molting and marsupial development was finely modeled, by detailing the influence of temperature on the probability of transition between all molt and embryonic stages along the female cycle. In addition, no effect of temperature or water hardness was detected on the number of oocytes and embryos carried by females. Furthermore, the finding that the relative durations of the first 4 molt and embryonic stages are constant whatever the temperature makes it possible to predict the molting dynamics in fluctuating temperature conditions. Because this could allow us to take into account the confounding influence of temperature on the measurement of reproductive markers, the implications of these findings for an optimal in situ implementation of the reproductive bioassay with G. fossarum are discussed. The relevance of this modeling approach during in situ implementation is tested in a companion study. Environ Toxicol Chem 2020;39:667–677. © 2019 SETAC